The challenge from physical attendance to virtual attendance in higher education during pandemic times - Ruiz-Aquino, Mely (2020)
In the face of the COVID-19 pandemic, economies are shutting down and paralyzed, and societies are facing rigid health measures such as social isolation, with its own effects, e.g., the suspension of face-to-face classes (which is a necessary protective measure for all students and teachers). We are living in uncertain times and we do not have an answer for everything, but the acceleration of virtualization is evident. This phenomenon has made it possible to sustain personal communications, entertainment activities at home and, in education, infodemia is expanding, with a heterogeneity of information through virtual and technological resources available for the teaching-learning process; however, unequal access has revealed the deep inequality that exists among students (Gallo, 2020), with a high digital gap between the richest and poorest quintiles.